Pangur Bán, Translations, Postmodernism, Paul Muldoon - Moi, Ruben (Nordlit, 2022)
«Pangur Bán» is probably the best know poem in Celtic studies, and a poem that tends to become increasingly more popular to audiences outside of Ireland. However, the anonymous, medieval poem has been cherished throughout history for a wide range of poetic, philosophical, intellectual and educational reasons. To inquire into the longevity and popularity of a marginal gloss on his cat by an Irish monk in a German monastery in the ninth century seems appropriate at a time when contemporary literature and applied hermeneutics of all kinds tend to dominate the literary discourses. This essay relates the historical poem to its many translations, for example by Paul Muldoon and Seamus Heaney, and current literary discourses. Why has this enigmatic jeu d’esprit been translated so frequently and why are these translations important? This essay argues that «Anonymous: Myself and Pangur», Muldoon’s version of «Pangur Bán», can be read as a prismatic poem for postmodernist concerns, in his own poetry and in recent theories.